Psychometric Evaluation of the Sociocultural Attitudes Towards Appearance Questionnaire-3 (SATAQ-3) among Adolescents - Amaral, Ana Carolina Soares (2016)
The objective of this study was to obtain estimates of the psychometric properties of the Sociocultural AttitudesTowards Appearance Questionnaire-3 in a sample of Brazilian adolescents. The sample consisted of 600 adolescents (254 boys),who participated in different stages of the research: assessment of verbal comprehension, construct validity, convergent validityand reliability, and evaluation of the reproducibility (test-retest). The adolescents showed adequate verbal comprehension of allitems. The scale presented a factor structure composed of seven factors (Î± > 0,40), with acceptable values of the fit indices ofthe model, significant positive correlation for the measures of body satisfaction (r = 0,41, p < 0,001), and reproducibility. Thepsychometric quality of the SATAQ-3 among adolescents was partially confirmed, and its use is indicated for this population.